Effect of fine content on shear strength of sand - Kho Joo, Tiong (Universiti Malaysia Sarawak, UNIMAS, 2005)
The present study aims the effect of fine content (passing 75μm sieve) on the shear strength characteristics of sand. To achieve this goal, three sand samples collected from different location of Sarawak, namely Batu Kitang, Sibu and Damai, were mixed with different percentages (i.e. 0%, 5%, 10%, 20% and 30%) of fine content. Direct shear test has been conducted to determine the shear strength parameters of these mixtures. For Damai sand, the fine content is less than 1%, hence effect of fine content on shear strength properties could not be studied. The results reveal that with the increase of fine content, the angle of internal friction, φ, values decreases for all the mixed sand samples. With the 30% increase of fine content, the angle of internal friction, φ, decreases by 35.18% and 38.61% for Batu Kitang Sand (DS-5) and Sibu Sand (DS-10), respectively. On the other hand, the cohesion value, c increases from 0.0552 kN/m2 to 12.33 kN/m2 and from 2.7453 kN/m2 to 11.065 kN/m2, were observed with the increase of fine content by 30%, for DS-5 and DS-10, respectively.